Problem-Based Learning Methods In Mathematics Courses: Systematic Literature Review - Istian, Nova Sri (IJBLE Scientific Publications Community Inc., 2025)
The purpose of this study is to determine and explain the impact of problem-based learning models on mathematical learning, namely achieving the achievement of mathematical learning goals. The method used in this study is a systematic method of literature review. From the results of the search strategy, 200 articles were found from 2010 to 2021, and were gradually systematically selected in 10 articles related to the topic of problem-based learning models in mathematics. The results of this study show that the impact of problem-based learning models claims mathematics learning. It shows that 10 tested articles can answer research questions. In other words, (1) How are mathematical learning goals achieved based on the results of reviews of research articles on problem-based learning models? (2) Do problem-based learning models affect the achievement of mathematics learning goals? The results and results of these articles show an increase in construction of mathematics learning goals after the implementation of problem-based learning models in mathematics. This means that (1) increase students' cognitive skills, (2) improve problem-solving capabilities, (3) increase student learning outcomes, and (4) increase student growth. These results demonstrate that there is an impact of problem-based learning models on mathematics learning.